Foot-ankle involvement of complex regional pain syndrome associated with pregnancy - Aydoğan Baykara, Rabia; Tuzcu, Göksel; Karabacak, Pınar; Küçük, Adem (The European Research Journal, 2019)
Complex regional pain syndrome (CRPS) is a condition which develops after a painful incident and characterized by allodynia/hyperalgesia, edema, skin anomalies and anomaly in blood flow and abnormal sudomotor activities independent of the precipitating incident. It is a rare condition in pregnancy and difficult to distinguish from pelvis and lower extremity pains which are inherent in pregnancy. Hips are typically involved, symmetrical involvement of feet and ankles are rarely reported; has a benign course however it is important to diagnose and treat due to fracture risk. Herein, we have presented a 28-year-old patient who came to us in week 32 of her pregnancy and gave birth in week 36 and diagnosed CRPS with bilateral involvement of foot and ankle.